Higher Education in Francophone Africa : What Tools Can Be Used to Support Financially-Sustainable Policies? - Gioan, Pierre Antoine (Washington, DC : World Bank, 2012)
The higher education and research sector in the French-speaking countries of Africa has, for more than a decade, been in a state of severe crisis, stemming from an increasing disparity between the requirements vital to providing high quality education and the available resources. The goal of this article is to: i) highlight the factors which have lead to the development of this situation in most countries; ii) identify the conditions for creating a framework to regulate the trends in the higher education and research systems and allow them to be more financially sustainable; and iii) identify ways of increasing funding for this sector as well maintaining its level of quality. The Main tools to support financially-sustainable policies include: i) controlling student inflows into higher education in order to avoid an increase in the student population that will be difficult to manage; ii) targeting student assistance more effectively towards the most disadvantaged and deserving students; iii) limiting the duration of study at the higher education level in order to prevent the number of students from building up in the institutions; iv) guiding students more effectively towards courses that offer better employment prospects; v) trying to promote a higher education private sector through fiscal and non-fiscal incentives; vi) reducing unit education costs; and vii) mobilizing additional self-generated resources.